2020
DOI: 10.1016/j.omtm.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

VEGFD Protects Retinal Ganglion Cells and, consequently, Capillaries against Excitotoxic Injury

Abstract: In the central nervous system, neurons and the vasculature influence each other. While it is well described that a functional vascular system is trophic to neurons and that vascular damage contributes to neurodegeneration, the opposite scenario in which neural damage might impact the microvasculature is less defined. In this study, using an in vivo excitotoxic approach in adult mice as a tool to cause specific damage to retinal ganglion cells, we detected subsequent damage to endothelial cells in retinal capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…These molecules are described to have dual effects by enhancing either protective or detrimental pathways. For instance, VEGF release, particularly the isoform VEGFA [ 179 , 180 ], in combination with reactive oxygen species (ROS) production in diabetic retinopathy has been shown to enhance retinal degeneration [ 181 ], whereas VEGFD is protective for RGCs and the retinal vasculature [ 182 ]. In addition, the secretion of TNF-α has been shown to exert early neuroprotective effects [ 183 ] but to ultimately induce Müller cell gliosis and RGC death in the glaucomatous retina [ 184 ].…”
Section: Glutamate Excitotoxicity In the Retinamentioning
confidence: 99%
“…These molecules are described to have dual effects by enhancing either protective or detrimental pathways. For instance, VEGF release, particularly the isoform VEGFA [ 179 , 180 ], in combination with reactive oxygen species (ROS) production in diabetic retinopathy has been shown to enhance retinal degeneration [ 181 ], whereas VEGFD is protective for RGCs and the retinal vasculature [ 182 ]. In addition, the secretion of TNF-α has been shown to exert early neuroprotective effects [ 183 ] but to ultimately induce Müller cell gliosis and RGC death in the glaucomatous retina [ 184 ].…”
Section: Glutamate Excitotoxicity In the Retinamentioning
confidence: 99%
“…Notably, elevated VEGF-C and VEGF-D levels were found in the retinal pigment epithelium (RPE) of patients with age-related macular degeneration (Vellanki et al, 2016). There are also data confirming a significant role of VEGF-D in retinal angiogenesis and ganglion cell protection under excitotoxic injury (Schlüter et al, 2020). In addition, it was demonstrated that hypoxia-induced expression of VEGF-C in the retina is as potent as VEGF-A in inducing pathological retinal neovascularization in PDR and retinopathy of prematurity (Campochiaro, 2015;Singh et al, 2015;Vellanki et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…These findings suggest that VEGF-D supplementation might be a novel, clinically applicable approach for neuronal and vascular protection [11]. However, the study by potentially explain that such effect is due to increased protection and vascular integrity [11], moreover, Schluter shows that VEGF-D has a positive effect on neuronal integrity [11].…”
Section: Discussionmentioning
confidence: 99%
“…Schluter et al [11] showed on mice model that in vivo VEGF-D supplementation via preserved the structural and functional integrity of retinal ganglion cells agains texcito toxicity and, additionally spared endothelial cells from degeneration [11]. Viral-mediated suppression of expression of the VEGF-D-binding receptor VEGFR3 in retinal ganglion cells revealed that VEGF-D exerts its protective capacity directly on retinal ganglion cells, while protection of endothelial cells is the result of upheld neuronalintegrity [11]. These findings suggest that VEGF-D supplementation might be a novel, clinically applicable approach for neuronal and vascular protection [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation